Fungal Biodiversity of Apple Bark, Leaves, Stems, and Fruit Under Rain Shelters with Reduced Fungicide Schedule - Claudia Maria Oliveira Longa; Lidia Nicola; Massimo Pindo; Elisa Bozza; Carmela Sicher; Daniel Bondesan; Ilaria Pertot; Michele Perazzolli (Agriculture)
The use of rain shelters is a promising agronomic practice to protect crops from rainfall, reducing the need for fungicides to control certain pathogens that take advantage of leaf wetness. However, the combined condition of absence of rain and reduced fungicide schedule can affect the fungal populations, possibly favoring biocontrol agents and/or other pathogens. In this study, the effects this practice on epiphytic and endophytic fungal communities associated with barks, leaves, flowers, and fruits of two apple cultivars (Fuji and Golden Delicious) were evaluated across two seasons. Apple plants were grown under two conditions in a commercial-like orchard: (1) covered by rain shelters with reduced fungicide schedule and (2) uncovered with standard integrated pest management (IPM) schedule. The use of rain shelters combined with reduced fungicide applications affects the overall fungal community structure and their abundance of specific taxa. Leaf epiphytes were the most impacted community, and fungal communities also differed between the two apple cultivars. The use of rain shelters helped reduce fungicide input in the orchard, but it increased the abundance of potential pathogens compared to the IPM in open field conditions, such as powdery mildew and apple scab. Understanding how the plant microbiome responds to new practices that help in reducing fungicides can help developing strategies that avoid the build-up of potentially new pathogens.